The effect of corporate share ownership on its share price (Analytical study in a sample of companies listed on the Iraq Stock Exchange) - Maha Abdul Kareem Mahdi; Salaheldeen Moammed AL- Emam (Journal of Madenat Alelem University College, 2022)
The research aimed to measure and analyses the effect of share ownership on its share prices in the Iraq Stock Exchange through a time series for the period from (2012-2020). The research sample consisted of twenty companies listed on the Iraq Stock Exchange that meet the requirements of the study. By sectors (the banking sector by eight banks, the agricultural sector by two companies, the tourism sector and hotels by three hotels, the industrial sector by four companies, the service sector by two companies, and the communications sector by one company) and statistical methods were used to test the normal distribution and test the correlation analysis and use the Pearson correlation coefficient. A number of results were reached, which showed the existence of a weak inverse relationship between the ownership of foreign shareholders and share prices, and showed the existence of a medium-strength inverse relationship between the ownership of Iraqi shareholders and share prices. Thus, the greater the ownership of Iraqi shareholders, the higher the share price and vice versa.